INTELLIGENT SYSTEM OF PRODUCTS DELIVERY THROUGH INTEGRATION OF ARTIFICIAL VISION, MOBILE ROBOTICS AND FLEXIBLE MANUFACTURING SYSTEM (FMS) - Cháux Cedeño, Julián Réne
With the arrival of the fourth industrial revolution also called Industry 4.0, whose main objective is the implementation of a large number of intelligent factories, capable of greater needs adaptability and production processes, as well as a more efficient allocation of resources, it is important, as a training institution in new technologies, to take a decisive role in the acceleration of entrepreneurship in the transition to industries 4.0; Therefore, it is proposed to use new technologies in the processes of the Flexible Manufacturing System (FMS), with which the FACT FESTO environment of the Centro de la Industria, la Empresa y los Servicios SENA Regional Huila counts. The system consists of a man-machine environment developed to be run from a Tablet, where the users can select their order and will be supervising the entire dispatch process, the products that in this case will be three pieces of work with different characteristics, red and black plastic pieces, and metallic pieces, will be found in a warehouse, once the users select their order, an autonomous mobile robot will move to the warehouse and find the location of the piece to be transported by means of an artificial vision algorithm that will identify the color characteristics , the piece will be transported to the FMS, where only the relevant modular systems will be enabled, making the process more efficient and having the tracking of the product to be delivered in real time.